(untitled) (Isagoge - Journal of Humanities and Social Sciences, 2022)
The hermeneutic circle between the word and life is life-giving, as it is an existential circle, based on the intrinsic relationship between the life of the word and the word of life, which manifests itself in the smallest of the human soul. Based on this principle, a new and challenging proposal of biblical hermeneutics emerges, which places itself on the limits between theological, linguistic and philosophical science, intending to re-ascend in contemporary times the inestimable value of sacred texts as a source of meanings and models that serve man as a source. of inspiration, rescuing from the characters and actions described in biblical sources, especially in the parables of the Kingdom, new meanings for human life. Thus, the hermeneutic process finds its dynamism in the relationship between word and life, becoming an existential circle.